Arrival or transient spaces?: differentiated politics of mobilities, socio-technological orderings and migrants’ socio-spatial embeddedness - Bork-Hüffer, Tabea; Bunchuay-Peth, Simon (Urban planning, 2020)
For the last decade there has been a lively debate on urban arrival spaces. Saunders’ (2011) widely received book Arrival Cities can be seen as catalyst of this debate. Taking a hitherto largely unexplored comparative approach, based on two empirical research studies on migrant workers and highly-skilled migrants in Singapore, this study debates the notion of arrival cities and spaces and argues for a differentiated perspective on the complex and interdependent processes of spatially and socially arriving. By comparing how the politics of mobilities, migration management and differential inclusion influence the migration trajectories of workers and professionals we argue that the concept of transient spaces might be a more fruitful approach for understanding the differentiated processes of arriving and (not) becoming socio-spatially embedded. In order to educe the relevance of a processual perspective, and for a systematic comparison, we apply four analytical dimensions that shed light on the process of migrating, arriving, and passing through. These four dimensions comprise (1) arriving, (2) settling, (3) mingling locally and translocally, and (4) planning ahead for future mobilities. We argue that the scholarship on politics of mobilities needs to take note of the combined effects of states’ and companies’ neoliberal politics of mobility throughout the migration process, and of the increasing relevance of socio-technological orderings, which imprint migrants’ socio-spatial embedding.
Gesehen am 16.04.2025